Imaging of Clival Hypoplasia in CHARGE Syndrome and Hypothesis for Development: A Case-Control Study - de Geus, C.M.; Bergman, J.E.H.; van Ravenswaaij-Arts, C.M.A.; Meiners, L.C. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: We present the largest case series to date on basiocciput abnormalities in CHARGE syndrome (Coloboma of the eye, Heart defects, Atresia of the choanae, Retardation of growth and/or development, Genital and/or urinary abnormalities, and Ear abnormalities and/or deafness). We aimed to show that basiocciput abnormalities are common and may aid in diagnosis. We furthermore explored whether clivus size correlates with the type of chromodomain-helicase-DNA binding protein 7 gene (CHD7) mutation, which causes CHARGE syndrome, and with clinical criteria according to Blake et al and Verloes.MATERIALS AND METHODS: We retrospectively analyzed the clivus of 23 patients with CHARGE syndrome with CHD7 mutations on MR imaging or CT. We recorded the size of the clivus, the Welcher angle, basilar invagination, and Chiari I malformations. We compared the clival size and Welcher angle of patients with CHARGE syndrome with those of 72 age-matched controls. Additionally, we tested for correlations between clivus size and mutation type or clinical criteria.RESULTS: Eighty-seven percent of the patients with CHARGE syndrome had an abnormal clivus; 61% had a clivus >2.5 SD smaller than that of age-matched controls. An abnormally large Welcher angle was observed in 35%. Basiocciput hypoplasia was found in 70%, and basilar invagination, in 29%. None of the patients had a Chiari I malformation. At the group level, patients with CHARGE syndrome had a smaller clivus and larger Welcher angle than controls. No significant correlation between clivus size and mutation type or clinical criteria was found.CONCLUSIONS: Most patients with CHARGE syndrome have an abnormal clivus. This suggests that clivus abnormalities may be used as an additional diagnostic tool. Our results provide evidence that CHD7, which is expressed in the presomitic mesoderm during somitogenesis, plays an important role in the formation of the clivus.Ba-XsexosphenobasionBa-EsendosphenobasionCHARGEColoboma of the eye, Heart defects, Atresia of the choanae, Retardation of growth and/or development, Genital and/or urinary abnormalities, and Ear abnormalities and deafnessCHD7chromodomain-helicase-DNA binding protein 7 gene. The animal homologue is Chd7. Non-italicized CHD7 (human) and Chd7 (animal) refer to the protein.